2000
DOI: 10.1038/sj.ejcn.1600885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soy as tofu vs meat on lipoprotein concentrations

Abstract: Objectives: To investigate the effect of replacing lean meat with a soy product, tofu, on serum lipoprotein concentrations. Study and design: Randomized cross-over dietary intervention study. Subjects: Forty-two free-living healthy males aged 35 ± 62 y completed the dietary intervention. Three additional subjects were non-compliant and excluded prior to analysis. Interventions: A diet containing lean meat (150 gad) was compared with one with 290 gad tofu in an isocaloric and isoprotein substitution. Both diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Based on the data of Ashton and Ball (Ashton & Ball, 2000), it was predicted that a sample size of 40 subjects would be sufficient to detect a change of 5% in total serum cholesterol with a power of 80% and a ¼ 0.05. A total of 44 subjects were recruited to allow for a 10% dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data of Ashton and Ball (Ashton & Ball, 2000), it was predicted that a sample size of 40 subjects would be sufficient to detect a change of 5% in total serum cholesterol with a power of 80% and a ¼ 0.05. A total of 44 subjects were recruited to allow for a 10% dropout.…”
Section: Discussionmentioning
confidence: 99%
“…One study (Teede et al, 2001) reports 'basic compound plus respective glycosides', which we divided by 1.666 to convert them to aglycone units. In three studies, the isoflavone form was not reported (Ashton & Ball, 2000;Vigna et al, 2000;Van Horn et al, 2001). Isoflavone contents were measured in all studies except that by Ashton and Ball (2000), who used a literature value.…”
Section: Study Selectionmentioning
confidence: 99%
“…In three studies, the isoflavone form was not reported (Ashton & Ball, 2000;Vigna et al, 2000;Van Horn et al, 2001). Isoflavone contents were measured in all studies except that by Ashton and Ball (2000), who used a literature value. Values for the concentrations of total, LDL and high-density lipoprotein (HDL) cholesterol in serum were divided by 1.029 to convert them to plasma values (Laboratory Methods Committee of the Lipids Research Clinics Program, 1977).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations